Inclusive Education in Costa Rican Academic Discourse: A Systematic Review of Meanings (2018-2025) - Navarro-Guillén, María Isabel (2026)
This article explores the meanings attributed to the concept of inclusive education through a systematic review under PRISMA criteria and a content analysis. The study examined categories associated with inclusive discourse, identifying tensions, convergences, and conceptual gaps. The findings show that although there is consensus on the importance of inclusive education as a human right and educational principle, a unified conceptual framework has not been consolidated. Predominant approaches describe it as an ongoing process, philosophy, stance, paradigm, or movement, which broadens its semantic scope but generates ambiguity and dispersion in its application. The analysis highlights an emphasis on the category “disability,” which appears more frequently than “inclusive education” itself, reflecting the persistence of a perspective inherited from special education and a reductionist view of diversity. In contrast, categories such as “social justice,” “equity,” or “inequality” are scarcely present, revealing limited attention to the structural dimensions of exclusion. The study concludes that inclusive education in Costa Rica is configured more as an aspirational horizon than as a consolidated epistemological category, posing the challenge of advancing toward clearer definitions that coherently guide educational policies and practices.